How the Wnt signaling pathway protects from neurodegeneration: the mitochondrial scenario - Arrázola, Macarena S.; Silva-Alvarez, Carmen; Inestrosa, Nibaldo C. (Frontiers in Cellular Neuroscience, 2015)
Alzheimer´s disease (AD) is the most common neurodegenerative disorder and is characterized by progressive memory loss and cognitive decline. One of the hallmarks of AD is the overproduction of amyloid-beta aggregates that range from the toxic soluble oligomer (Aβo) form to extracellular accumulations in the brain. Growing evidence indicates that mitochondrial dysfunction is a common feature of neurodegenerative diseases and is observed at an early stage in the pathogenesis of AD. Reports indicate that mitochondrial structure and function are affected by Aβo and can trigger neuronal cell death. Mitochondria are highly dynamic organelles, and the balance between their fusion and fission processes is essential for neuronal function. Interestingly, in AD, the process known as “mitochondrial dynamics” is also impaired by Aβo. On the other hand, the activation of the Wnt signaling pathway has an essential role in synaptic maintenance and neuronal functions, and its deregulation has also been implicated in AD. We have demonstrated that canonical Wnt signaling, through the Wnt3a ligand, prevents the permeabilization of mitochondrial membranes through the inhibition of the mitochondrial permeability transition pore (mPTP), induced by Aβo. In addition, we showed that non-canonical Wnt signaling, through the Wnt5a ligand, protects mitochondria from fission-fusion alterations in AD. These results suggest new approaches by which different Wnt signaling pathways protect neurons in AD, and support the idea that mitochondria have become potential therapeutic targets for the treatment of neurodegenerative disorders. Here we discuss the neuroprotective role of the canonical and non-canonical Wnt signaling pathways in AD and their differential modulation of mitochondrial processes, associated with mitochondrial dysfunction and neurodegeneration.